Pengaruh Discovery Learning Berbasis Catur Pramana Terhadap Keaktifan dan Hasil Belajar Pendidikan Agama Hindu - Oktaviani Arta, Ni Putu Eka; Dantes, I Nyoman; Lisna Handayani, Ni Nyoman (Kamaya: Jurnal Ilmu Agama, 2025)
Low levels of student engagement and learning outcomes in Hindu Religious and Character Education remain a fundamental challenge in delivering meaningful and value-based instruction. One contributing factor is the dominance of conventional teaching approaches that limit active student involvement and offer little space for exploring the deeper meanings of religious teachings. This study aims to examine the effect of the Discovery Learning model integrated with the epistemological cycle of Catur Pramāṇa on the engagement and learning outcomes of fifth-grade students in Cluster V, Sukasada District. Catur Pramāṇa, a reasoning method in Hindu philosophy, consists of four sources of knowledge—Pratyakṣa, Anumāna, Upamāna, and Śabda—which were adopted as instructional syntax to foster both scientific reasoning and spiritual understanding. A quantitative approach was employed using a quasi-experimental posttest-only control group design. A total of 57 students were randomly selected and divided into experimental and control groups. The experimental group received instruction through Discovery Learning based on Catur Pramāṇa, while the control group was taught using conventional methods. Data were analyzed using MANOVA. The results indicated significant effects on student engagement (F = 40.481), learning outcomes (F = 19.404), and both variables simultaneously (F = 32.792) with p < 0.05. The study concludes that this model is effective in enhancing student participation and conceptual understanding, and is suitable for value-based Hindu education. These findings have practical implications for developing instructional strategies in Hindu Religious Education that are more contextual, reflective, and transformative.